Antifungal and antitermitic potential of extracts of industrial wood waste from Central Amazon, Brazil - Brocco, Victor; Costa, Lais; Cristina Monteiro de Castro, Marcelly; Barbosa, Andressa Vitoria Xavier; Henrique da Costa Lyra, Pedro; Alves Cruz da Conceição, Rennata Crystine (Maderas. Ciencia y Tecnología, 2024)
Studies on wood durability have highlighted the use of new environmentally friendly substances. In this sense, research carried out with Amazonian forest species is extremely important for the discovery of new bioactive substances from durable wood and its residues. The aim of this study was to evaluate the antitermitic and antifungal potential of extracts obtained from industrial processing residues of wood species from Central Amazonia, Brazil. The sawdust of seven Amazonian wood species were collected to obtain extracts and quantify the extractive content. The extracts produced were tested for inhibition of fungal growth of Rhodonia placenta and Trametes versicolor and impregnated in low natural durability wood known as Simarouba amara (marupa) to verify the effect on wood natural durability against Nasutitermes sp. termites and Gloeophyllum trabeum fungus. Simarouba amara (marupa) wood was easily impregnated and showed satisfactory retention values. The species Buchenavia sp., Dinizia excelsa (red angelim), Hymenolobium flavum (angelim pedra) and Manilkara elata (maçaranduba) exhibited high contents of secondary metabolites. It was observed that the extracts of Roupala montana (louro faia) and Hymenolobium flavum (angelim pedra) exhibited the best performance in inhibiting fungal growth. In the accelerated decay test, marupa wood impregnated with Buchenavia sp. (tanimbuca) extract showed the lowest weight loss after exposure to the fungus Gloeophyllum trabeum. In the termite choice feeding test, wood impregnated with Dinizia excelsa (red angelim) and Buchenavia sp. (tanimbuca) extracts were most consumed and the extracts of Roupala montana (louro faia), Cordia sp., Hymenolobium flavum (angelim pedra) and Manilkara elata (maçaranduba) provided greater inhibition of termite attack. The combination of extracts must be tested in future studies to verify the synergistic effect, in addition to the chemical analyses of the selected extracts.